PENGEMBANGAN INSTRUMEN SOAL BERBASIS GOOGLE FORM PADA MATERI PEMANASAN GLOBAL KELAS VII SMP - Hasbah; Nur Kuswanti; Lina Arifah Fitriyah Fitriyah (Metalanguage: Jurnal Ilmu Bahasa dan Sastra Indonesia, 2022)
Teaching and learning activities during the current pandemic require the learning process to be carried out using a remote method with an online system. Evacuation of learning must also be done online during the Covid-19 pandemic. One of the online methods in evaluating learning is the google form.The objectives to be achieved from this research are to describe the process of developing a google form-based question instrument for global warming class VII SMP/MTS and describe the results of products that have passed the validation process. This research is a type of development research, using the ADDIE model.The results of the study showed (1) the google form-based question instrument was included in the valid category of 92%. (2) 10 multiple-choice questions that were developed obtained 1 valid item; reliability 0.80 discriminatory power with good category there are 9 questions, namely number 1, 3, 4, 5, 6, 7, 8, 9, and 10 and questions with poor discriminating power are in question number 2; 10 items that have been tested are classified in the difficult category consisting of 7 items and the moderate category there are 3 items; 10 items containing distractors really work